Diverse nitrogen acquisition strategies of conifer-associated ectomycorrhizal fungi shape unique responses to changing nitrogen regimes - Lofgren, Lotus; Maillard, François; Michaud, Talia; Gredeby, Alice; Tunlid, Anders; Kennedy, Peter G. (Frontiers in Plant Science, 2025)
Ectomycorrhizal fungi are critical mediators of nitrogen acquisition in forest ecosystems, exhibiting variation in both host association and metabolic traits that mediate differential responses to forest nitrogen availability. However, how nitrogen acquisition strategies vary among closely related fungal species, how these patterns manifest in conifer-associated ECM fungi, and whether they persist over changing nitrogen regimes, remains poorly understood. Using an integrative approach combining in silico genomic analysis, in vitro growth assays, and isotopic analysis of in situ specimens spanning six decades, we provide the first comprehensive examination of nitrogen assimilation in congeneric conifer-associated ectomycorrhizal fungi using six Suillus species. We found highly conserved genes for inorganic nitrogen assimilation across species, but striking interspecific variation in the genetic capacity for organic nitrogen metabolism. Interspecific differences were also observed in fungal growth on varying nitrogen substrates in the growth assays, as well as in the isotopic signatures of historical specimens. For the latter, carbon isotopic patterns showed divergent temporal trends among Suillus species, suggestive of differential N use over time. Collectively, these genomic, physiological, and isotopic findings support the presence of notable interspecific diversity in ectomycorrhizal fungal nitrogen acquisition and suggest that coniferous forests and their fungal symbionts exhibit distinct responses to shifts in nitrogen availability compared to broadleaf forests. The ability of even closely related ectomycorrhizal fungi to employ diverse nitrogen acquisition strategies has important implications for forest ecosystem resilience, as different species may provide complementary services to host trees under varying environmental conditions, potentially reducing competition, and influencing forest responses to altered nutrient availability.